DIGITAL LOGIC - CHITAMBARA RAO K; PILLA RAMANA; KIRAN KUMAR P (BANGALORE PEN PRESS INTERNATIONAL, 2025)
KEY FEATURES OF THE BOOK:- 1. COMPREHENSIVE COVERAGE 2 CONCEPT CLARITY 3. PRACTICAL DESIGN APPROACH 4. MINIMIZATION TECHNIQUES 5. HANDS -ON EXAMPLES 6. SEQUENTIAL CIRCUIT DESIGN 7. MEMORY & PLDs 8. LOGIC FAMILIES 9. ERROR DETECTION & CODING
ECE, EEE AND CSE
ELECTRONICS AND COMMUNICATION
Keywords: ELECTRONICS; COMPUTERS